Augmented Reality Technology For Arabic Vocabulary Learning As A Model Of Quran Reflection For Hearing Impairment Adults - Ahmad Yusoff, Nabilah Fasihah; Abas, Ummu Hani; Jaffar, Mohammad Najib; Mat Ali, Ahmad Asyraf; Md. Noor, Mohammad Lukman Al-Hakim; Abdul Hanid, Mohd Fadzil; Raus, Norakyairee Mohd (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study uses innovative Augmented Reality Technology to analyze a new model design of Quranic reflection through learning Arabic vocabulary for adult learners with hearing impairments. Learning the Arabic vocabulary contained in the Al-Quran and understanding its meaning will facilitate the process of reading, understanding, memorizing, and practicing it. Nevertheless, Tadabbur Al-Quran, through a vocabulary approach based on Augmented Reality Technology for deaf adult learners, has still not been researched and developed. Therefore, a new model should be well-designed and appropriate to their needs and preferred learning styles. This study uses the needs analysis model of Hutchinson and Waters, 1987 which consists of Lacks, Needs, and Wants to collect data. The study findings show that most respondents do not know the Arabic vocabulary in Juz 30 related to humans, animals, plants, and other natural creations and phenomena. In addition, most of them agreed to learn the Arabic language in Juz 30 with the help of AR technology. This study will provide a practical learning experience for adult learners with hearing impairments using Augmented Reality Technology.